Retinal Pigment Epithelium Rip Following Serial Intravitreal Injections of Avastin - Jawad bin Yamin Butt, Muhammad Tariq Khan, Tariq Mehmood Qureshi, Khalid Mehmood (Pakistan Journal of Ophthalmology, 2011)
Anti-vascular endothelial growth factor (anti- VEGF) therapy has tremendously improved the management of wet age-related macular degeneration (AMD). With an increase in the usage of such agents over the last few years, complications have also been noted. It has been reported that retinal pigment epithelium (RPE) rip can occur following intravitreal injection of bevacizumab and other anti- VEGF agents1,2. We would like to share our experience with intravitreal injection of bevacizumab (1.25 mg/0.05 ml) in a patient